2006
DOI: 10.1016/j.molcel.2005.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Pathways and Phenotypes by Systematic Gene Overexpression

Abstract: Many disease states result from gene overexpression, often in a specific genetic context. To explore gene overexpression phenotypes systematically, we assembled an array of 5280 yeast strains, each containing an inducible copy of an S. cerevisiae gene, covering >80% of the genome. Approximately 15% of the overexpressed genes (769) reduced growth rate. This gene set was enriched for cell cycle-regulated genes, signaling molecules, and transcription factors. Overexpression of most toxic genes resulted in phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
711
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(783 citation statements)
references
References 63 publications
55
711
1
4
Order By: Relevance
“…This protein was identified via a synthetic dosage lethality screen in a pho85D and a pho80D strain and localization and phosphorylation studies confirmed that Pho85-Pho80 promotes nuclear exclusion of Crz1 via direct phosphorylation (Sopko et al 2006). Crz1 is known to be activated via dephosphorylation by the serine/threonine protein phosphatase Calcineurin, consisting of two catalytic subunits Cna1 and Cna2 and a regulatory subunit Cnb1, in response to ion stress involving Li ?…”
Section: The Protein Kinase Sch9mentioning
confidence: 99%
“…This protein was identified via a synthetic dosage lethality screen in a pho85D and a pho80D strain and localization and phosphorylation studies confirmed that Pho85-Pho80 promotes nuclear exclusion of Crz1 via direct phosphorylation (Sopko et al 2006). Crz1 is known to be activated via dephosphorylation by the serine/threonine protein phosphatase Calcineurin, consisting of two catalytic subunits Cna1 and Cna2 and a regulatory subunit Cnb1, in response to ion stress involving Li ?…”
Section: The Protein Kinase Sch9mentioning
confidence: 99%
“…With regard to the latter, the yeast genome contains approximately 1130 essential genes, and we readily envision application of our platform to this important yeast gene set. The resulting mutant collection will provide a strong complement to existing genome-wide collections of titratable promoter alleles (Mnaimneh et al, 2004), gene deletion mutants (Winzeler and Davis, 1997;Winzeler et al, 1999) and gene overexpression strains (Sopko et al, 2006;Gelperin et al, 2005). Similarly, genome-scale mislocalization screens will augment pathway discovery tools, such as synthetic genetic array analysis (Tong et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Rad2p-induced cell growth arrest and consequent mitotic catastrophe would be exaggerated phenotypes that do not occur under natural growth conditions, regardless of the presence of DNA damage. It has recently been shown that overexpression arrays are useful for studying gain-of-function phenotypes of genes that cannot be examined by traditional gene deletion studies (Sopko et al, 2006). Thus, overexpression of Rad2p can elucidate the gain-of-function of Rad2p that is shown only temporarily while it is induced by DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…RAD2 is induced naturally by DNA-damaging agents (Madura and Prakash, 1986;Robinson et al, 1986), and artificial overexpression of the gene interrupts cell growth (Nicolet and Friedberg, 1987;Sopko et al, 2006). Indeed, serially cultured RAD2-overexpressing cells confer rapid growth and the rapidly growing cells express less RAD2 (Nicolet and Friedberg, 1987).…”
Section: Introductionmentioning
confidence: 99%